(untitled) (World Economics and Finance Bulletin, 2025)
To accomplish these goals, this study used a descriptive technique (Quantitative research methodology) to ascertain the status of educational institutions in Iraq and Baghdad and the potential contribution of e-marketing to their improvement. Information was gathered from the institutes’ producers and clients at the same time, as well as from a sample of 400 respondents who completed a survey Because these institutions lack essential elements of the emarketing mix, websites and their disinterest in the most crucial and primary ranking factor, educational institutions in Iraq and Baghdad have struggled to flourish. Increase the awareness of workers in educational institutes about the role of good marketing of educational services electronically and Work to reduce the gap in the capabilities of applying electronic marketing in educational institutes compared to private ones and encourage the application of electronic marketing in both private and public education, as well as aiding educational institutions that promote education services electronically and introducing the community to the importance of applying electronic marketing and the advantages that can be achieved through the application process and the necessity of conducting intensive and advanced studies in this field related to developing educational services through marketing them electronically. and Focusing light on the modern mechanisms used in marketing educational services and knowing what is new in this field Strengthening the capabilities of public educational institutes and reducing the gap between them and private educational institutes Keeping abreast of developments and preparing more studies on this topic. The opinions of the respondents are the primary emphasis of the article, with particular attention paid to characteristics of websites such as design, clarity, and high-quality content. The article also looks at particular e-marketing tools including live chat, email newsletters, blogs, microsites, online publications, eBooks, and mobile applications, in addition to particular website features like design, clarity, and social elements. Recent studies show that educational institutions are shifting more and more of their marketing operations online, making effective use of online resources as a key component of their marketing strategies. These activities range from raising awareness to developing a top-notch virtual education system. The Internet must be used as a component of an integrated marketing communications strategy to be most effective. and the date range for this study is from May 2023 to December 2023. and study limits and implications to obtain comprehensive insights, the authors advise that additional study be done to evaluate the hypotheses in longitudinal research design. and Practical ramifications educational institutes in poor nations have been shown to give their strategic objectives less thought. goals Understanding how e-marketing affects organizational performance, as well as how e-marketing affects educational institute’s marketing performance, examining research on educational institutes, and determining how emarketing and organizational performance are related to each other.